(3ecGJHI GdTjN CHj GdcJGjHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3EYde jG CNj Cf Yedi hYedc jfXQ ajg ef dGjNja hdG jLhQ CeG JJMbb Cf ehdi GdNdb s
(3BNQgG (B:s
(3hdG JLYd acQ GdQOi dfaSc bGFOkG h OdjdkG hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B87s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds